(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
This article presents scientific information about the natural distribution of medicinal plants in Kyrgyzstan and the conditions of their collective growth with other plants of the natural reserve. Due to the increase in arable land in the country and the expansion of human economic activity, the number of wild medicinal plants is decreasing. It is recommended to require urgent protection along with the rational use of natural resources of medicinal plants in the republic and the rational use of the territories where they are distributed. In the course of research, together with the distribution of plants in natural conditions, it was established that the medicinal plant Patrinia intermedia grows in different habitats, and also showed details of plant communities.